Experience analysis and forms of alienation - Søren Nagbøl (Social Work and Society)
Based on the official Danish definition of alienation, this article explores contemporary forms of alienation through the prism of the history of ideas. It outlines the characteristic features of the experience society; that is, the replacement of a society characterised by labour and a scarcity of resources with a society of abundance, defined by a psychophysical semantics. This is illustrated through examples of tangible material stagings. To counteract the representation of the effects of alienation within dualist sociology and subjective idealist philosophy, process-sociological and experience-analytical models are introduced. As theoretical and practical means of orientation, these approaches show how forms of alienation can be deciphered, analysed and verbalised - in short, alienation is understood in terms of the figurations influencing the contexts of people's lives. Settings for educational sociological practice at Aarhus University are introduced in which students themselves decide on the themes and perform analyses that show how forms of alienation are staged and conducted. The article concludes with a look at how the diverse contemporary manifestations of forms of alienation are discussed within interdisciplinary discourses.